Multibit image watermarking algorithm resistant to geometric attacks based on level set method (Tongxin xuebao)
A multibit watermarking algorithm based on level set method was proposed.First,the stable location of the unit disk was found using level set method.Then,pseudo-Zernike moments were calculated.At last,the watermark was embedded by modifying the pseudo-Zernike moments.In the extraction process,the root-mean-square-error method was employed to detect the watermark.Simulation results show that the algorithm overcomes the defect of the traditional al-gorithm based on pseudo-Zernike moments,while be robust against geometric attacks.